CONTEMPORARIEST SYMBOLICS PADA PERILAKU BISNIS PEDAGANG DI LINGKUNGAN PASAR TRADISIONAL - Saudah Saudah (Jurnal Nomosleca, 2017)
AbstractTrader's business behavior in the traditional market environment is reflected in the behavior that appears in the interaction built with other parties. The uniqueness that is highlighted is the trade situation that can not be separated from face to face communication directly, began to be supported by advances in the field of communication technology. Contribution in building interaction among the parties involved is able to generate trust so that communication occurs continuously. What is in the business of the traditional market shows a recognizable and recognizable identity, by seeing the communication style of the merchant, the utilization of the communication tool, the accessories used, and the means of transportation. They are all symbols inherent in the life of the merchant, reflecting the life of the merchant. Meaning of the symbol by others is not much different, because people have the ability to give meaning and assessment of a person. This is the uniqueness of the merchant that is reflected in the daily behavior in the traditional market environment. Keywords: Symbols, Traders, Traditional MarketsDOI : https://doi.org/10.26905/nomosleca.v3i1.1485